Aktualisasi Nilai Sila Ketiga Pancasila: Menjaga Persatuan di Era Globalisasi yang Penuh Tantangan - Ture Ayu Situmeang; Yakobus Ndona (International Forum of Researchers and Lecturers, 2025)
Globalization is a term that has to do with the increasing interconnectedness and interdependence between nations and people around the world through trade, investment, travel, popular culture, and other forms of interaction, so that the boundaries of a country become increasingly narrow. The values of Pancasila, especially the values contained in the third principle, namely